23=-8x-7+2x

Simple and best practice solution for 23=-8x-7+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 23=-8x-7+2x equation:


Simplifying
23 = -8x + -7 + 2x

Reorder the terms:
23 = -7 + -8x + 2x

Combine like terms: -8x + 2x = -6x
23 = -7 + -6x

Solving
23 = -7 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
23 + 6x = -7 + -6x + 6x

Combine like terms: -6x + 6x = 0
23 + 6x = -7 + 0
23 + 6x = -7

Add '-23' to each side of the equation.
23 + -23 + 6x = -7 + -23

Combine like terms: 23 + -23 = 0
0 + 6x = -7 + -23
6x = -7 + -23

Combine like terms: -7 + -23 = -30
6x = -30

Divide each side by '6'.
x = -5

Simplifying
x = -5

See similar equations:

| 7(a+2)-5=7a+9 | | 6k+7=43 | | 2(x+3)=3(2x-10) | | -11x-8+3x=24 | | 2(-7x+6)=-16-7x | | 5.9x=-30.09 | | -5=7+4x | | 2c+3=4(5c-6) | | 4(2x+3)+5=1 | | -5x-4(-7-4x)=36+7x | | 60=4(5-x) | | 2(5+x)=-30 | | x-21=-x*2 | | 3(7x-7)=-6+6x | | 4x-148=3x+566 | | 50+0.9*(y-30)+10+10+28=y | | 5[2-3(x-8)]=26-8x | | (2x^4)+16x=0 | | 2x+(-4x)=22 | | 4x+9-49=0 | | -1+3(v-7)=-28 | | 2x^2+22x+60=x | | 20y+13=15y-8 | | 4x+4x=64 | | (18a^3)-72a=0 | | z-0.45=5.97 | | 3a+(4b+2)I=9-6I | | 50+0.9*(y-30)=y | | -5x+24=-8(x-6)+6x | | -(-a)= | | 3x(4)=2 | | -n+n= |

Equations solver categories